The determinants of contraceptive use in Zambia - Fushayi, Nelly (University of Cape Town, 2014)
Includes bibliographical references (leaves 62-64). === The contraceptive prevalence rate in Zambia is high, while fertility decline is very slow. From 1992 to 2007, the contraceptive prevalence rate (CPR) increased from 8.9 per cent in 1992 to 32.7 per cent in 2007; while total fertility rate (TFR) fluctuated between 6.5 and 6.2. The study uses three Zambian Demographic and Health Survey (DHS) data sets for 1996, 2001-2 and 2007 and applies multivariate logistic regression techniques to identify factors affecting the use and choice of modern contraceptives by Zambian women. The study seeks to identify how contraceptive use in Zambia influences fertility and why both contraceptive use and fertility are high. In our results, place of residence (urban/rural), age, education, number of living children and formal employment were identified as factors that are significantly related to use of modern contraceptives.